Postoperative morbidity and 3 year mortality in diabetic patients undergoing CABG - Nyi Nyi, Naing; Wan Arfah Nadiah, Wan Abdul Jamil; Sani, Mohamad Ikhwan (2020)
BSTRACT Objective: To determine the impact of diabetes mellitus on 30 day postoperative morbidity and after three year mortality following CABG. Design: A cross sectional study. Materials and Methods: A total of 205 patients who underwent CABG from January 2002 until December 2005 at Cardiothoracic Unit of Hospital Universiti Sains Malaysia (HUSM) was conducted. Patients who underwent emergency CABG, concomitant valve or other surgery during CABG and redo cases were excluded. Patients who underwent operation in other hospital were also excluded even though being follow up in HUSM. The data was analyzed by using multiple logistic regression. Results: Out of 205 patients, 90 of them (43.9%) suffered from Type 2 Diabetes Mellitus. Analysis showed that diabetes mellitus did not give impact towards 30 day mortality after adjustment of potential risk factors (COAD, BMI, ejection fraction, cardiopulmonary bypass time and length of ICU stay) (Adjusted odds ratio 4.15; 95% CI: 0.87, 19.80; P = 0.074). The analysis also showed that diabetes mellitus did not give impact towards the three year mortality after adjustment of risk factors (Adjusted odds ratio 1.71; 95% CI: 0.52, 5.66; P = 0.380). Conclusion: This study could be the pioneer for local population to collect our own database before subsequent studies can be done especially in improving the management strategies for diabetic patient with coronary artery disease.